Food safety management system EN ISO 22000:2005 - Soares, N. (2016)
The introduction of international standard ISO 22000:2005 presents four key elements that are present throughout the norm: interactive communication, system management, prerequisite programs, and hazard analysis critical control point (HACCP) principles. These are fundamental to guarantee food safety in every part of the food chain. The standard identifies methods of how top management should demonstrate its commitment to the development, implementation, and update of the food safety system. Top management should ensure the constant integrity of the food safety management system (FSMS) whenever updates are implemented. It is important to emphasize that planning is fundamental to the success of the FSMS. Although resource management is presented in ISO 22000:2005 separately from management responsibility, it is clear that it is one of the top management obligations. ISO 22000:2005 determines that organizations seek to continuously improve and update the FSMS.